(untitled) (Filološke studije, 2019)
The present article deals with the analysis of theoretical bases of synergetic linguistics. The synergetic linguistics is a new subdiscipline of system theory, which purpose is creation of the dynamic theory of language. The methodology of the given direction in modern linguistics is based on Hempel-Oppenheims Deductive-Nomological Model of Scientific Explanation which is realized in synergetic linguistics in the framework of the functionalanalytical approach. The primary aim of synergetic linguistics consists in discovering of latent mechanisms of language and an establishment on this basis of immanent laws of language. The concept of the law is key concept in the synergetic linguistics because this concept allow to create a unified basis for the description of language and thus to leave on formation of the unified theory of language.